U-slot rectangular patch antenna for dual band application - Habib, Mohammad Shawkat; Islam, Md. Rafiqul; Abdullah, Khaizuran; Jakpar, M. Jamil (Springer International Publishing, 2015)
Dual and multi-band rectangular microstrip antennas can be realized by cutting U slots inside the patch. In this paper, the length and width of U-slots are optimized in order to achieve dual-band and multi-band. Computer Simulation Technology (CST) software was used to design, simulate and optimization of antenna. Two resonant frequencies at 1.8 GHz and 2.4 GHz were found with reasonable gain. Additional resonant frequencies could also be achieved from 2.8 to 3.0 GHz using the similar approach.